FRASA EKSOSENTRIS BAHASA MELAYU RIAU SUBDIALEK KAMPAR - Rizaldi, Dedi; Mustafa, M. Nur; Faizah, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to examine and describe the exocentric phrases of Riau Malay subdialek Kampar in the Village of Tanjung Rambutan Kampar Subdistrict Kampar District. The author is interested in researching and developing this problem, because it is seen at the present time has many native people, especially the younger generation began a few who really use the language Riau Riau subdialek Kampar as well as the original. Even many of the younger generation can not distinguish which is their native language with the language of the outer regions. The type of research used is qualitative with descriptive method. Technique of collecting data in this research is documentation. The data were collected by reading the folklore from Kampar regency, the data already obtained were translated into Indonesian, furthermore marking the data belonging to the exocentric phrase, the data is described in accordance with the theory used and after passing the above stages, the data is concluded. Based on the results of research, In research folklore Kampar district told by informants there are various forms of eksocentric phrases. The number of exocentric phrases found is 226 data. Exocentric phrases are directive there are 100 data, nonoconditional phrases are nondirektif there 57 data, and konocentric phrases konektif there 69 data.Keywords: Exocentric phrases, Riau Malay subdialek Kampar, folklore